Bibliometric overview of the systems approach in Geomorphology production: journals Q1 and Q2, Earth-Surface Processes (SJR) - Mota, Gabriel Santos da; Carrasco, Thayara Silveira; Santos, Jonathas Jesus dos; Rodrigues, Cleide (Revista Brasileira de Geomorfologia, 2025)
In the 20th century, the systems approach was consolidated as an alternative in proposing scientific methods and models in Geomorphology, but what is the extent of its influence and how did the appropriation of these concepts by the discipline manifest itself? This research aimed to provide a historical overview of the impact of the systems approach on the production in Geomorphology based on the bibliometric analysis of 20 journals classified as Q1 and Q2 (Scimago Journal Rank — SJR 2019) in the Earth-Surface Processes category. Data from the Web of Science Core Collection were processed using VOSViewer and statistical tools, totaling a sample field of 1129 documents. The results brought to light similarities and differences, whether in the protagonism of countries, authors, and subfields of the discipline. In general, there was a scenario of growth in the use of terms and concepts related to the systems approach in Geomorphology and a significant conceptual distance, with the loss of referential links with the past. Thus, even far from the unitary and transdisciplinary science idealized by Ludwig von Bertalanffy, systems approaches have been consolidated as part of the work of geomorphologists and geoscientists for decades, strongly driven by the use of models and quantitative methods.